B-cell receptor signalling and its crosstalk with other pathways in normal and malignant cells - Seda, Vaclav; Mraz, Marek (European journal of haematology, 2015)
The physiology of B cells is intimately connected with the function of their B-cell receptor (BCR). B-cell lymphomas frequently (dys)regulate BCR signalling and thus take advantage of this pre-existing pathway for B-cell proliferation and survival. This has recently been underscored by clinical trials demonstrating that small molecules (fosfamatinib, ibrutinib, idelalisib) inhibiting BCR-associated kinases (SYK, BTK, PI3K) have an encouraging clinical effect. Here we describe the current knowledge of the specific aspects of BCR signalling in diffuse large B-cell lymphoma (DLBCL), follicular lymphoma, chronic lymphocytic leukaemia (CLL) and normal B cells. Multiple factors can contribute to BCR pathway (dys)regulation in these malignancies and the activation of 'chronic' or 'tonic' BCR signalling. In lymphoma B cells, the balance of initiation, amplitude and duration of BCR activation can be influenced by a specific immunoglobulin structure, the expression and mutations of adaptor molecules (like GAB1, BLNK, GRB2, CARD11), the activity of kinases (like LYN, SYK, PI3K) or phosphatases (like SHIP-1, SHP-1 and PTEN) and levels of microRNAs. We also discuss the crosstalk of BCR with other signalling pathways (NF-κB, adhesion through integrins, migration and chemokine signalling) to emphasise that the 'BCR inhibitors' target multiple pathways interconnected with BCR, which might explain some of their clinical activity.
Keywords: signální transdukce; Signal Transduction; B-cell receptor; Humans; inhibitory proteinkinas; bruton tyrosine kinase; miRNA; receptory antigenů B-buněk; interakce mezi receptory a ligandy; Antineoplastic Agents; ZAP-70; NFκB; lidé; tyrosinkinasy; LYN; PI(3)K; chronická lymfatická leukemie; B-lymfocyty; Leukemia, Lymphocytic, Chronic, B-Cell; Protein Kinase Inhibitors; Protein-Tyrosine Kinases; difúzní velkobuněčný B-lymfom; B-Lymphocytes; regulace genové exprese u leukemie; Lymphoma, Follicular; Lymphoma, Large B-Cell, Diffuse; protinádorové látky; Receptors, Antigen, B-Cell; spleen tyrosine kinase; Receptor Cross-Talk; folikulární lymfom; B cell; ibrutinib; Gene Expression Regulation, Leukemic